1993
DOI: 10.1200/jco.1993.11.12.2434
|View full text |Cite
|
Sign up to set email alerts
|

Leukemoid reaction, bone marrow invasion, fever of unknown origin, and metastatic pattern in the natural history of advanced undifferentiated carcinoma of nasopharyngeal type: a review of 255 consecutive cases.

Abstract: The PNS described could help in the diagnosis and follow-up of UCNT patients because they may be the first manifestation of the disease or may reappear with relapse. BMI is a frequent finding in patients with metastases and is unrelated to PNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 39 publications
4
49
0
1
Order By: Relevance
“…In the nude mouse study, metastasis was only observed in the brain, cervical lymph nodes, and lungs, a distribution that does not mimic the human disease. Specifically, metastasis to the brain is not a clinical characteristic of NPC, 32 was not detected in our model, and may be accounted for in the nude mouse model by focal trauma caused by passing the needle through the hard palate. Thus, we have developed an orthotopic xenograft model of invasive and metastatic NPC disease that closely mimics human disease well enough to assist in further identifying cellular characteristics that direct aggressively invasive and disseminated growth as well as identifying effective targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In the nude mouse study, metastasis was only observed in the brain, cervical lymph nodes, and lungs, a distribution that does not mimic the human disease. Specifically, metastasis to the brain is not a clinical characteristic of NPC, 32 was not detected in our model, and may be accounted for in the nude mouse model by focal trauma caused by passing the needle through the hard palate. Thus, we have developed an orthotopic xenograft model of invasive and metastatic NPC disease that closely mimics human disease well enough to assist in further identifying cellular characteristics that direct aggressively invasive and disseminated growth as well as identifying effective targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Although nasopharyngeal carcinoma is classified as a subtype of head and neck squamous cell carcinoma, its unique epidemiology, clinical characteristics, etiology, and histopathology warrant separate efforts for the study of its underlying molecular mechanisms of carcinogenesis (1). For example, nasopharyngeal carcinoma patients tend to present at a more advanced stage of disease because the primary anatomical site of tumor growth is located in a silent area, and they exhibit higher metastatic potential when compared with other head and neck squamous cell carcinoma (3)(4)(5). In addition, a strong association of EBV and nasopharyngeal carcinoma has been widely accepted (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophilia is frequently seen in large cell lung cancer (2), although it has been reported in association with a variety of tumors (3-7), particularly in the presence of marrow involvement (8,9). The leukocytosis is usually modest, in the range of 12-30×10 3 / l, although levels as high as 100× 10 3 / l have been reported (10).…”
Section: Discussionmentioning
confidence: 99%